'The life of individuals as well as of nations': international law and the League of Nations' anti-trafficking governmentalities - Legg, Stephen (Cambridge University Press, 2012)
This paper will address an often-neglected agenda of the much-derided League of Nations: its ‘social’ and ‘technical’ works. These targeted human security through regulating different forms of international mobility, including the fight against trafficking in women and children. The League used conventions and conferences to commit nation-states, in a legal model, to standardized anti-trafficking measures. It also, however, worked to educate and inform states, voluntary organizations, and the general public about the nature of trafficking and the ways of combating it. The latter techniques are here interpreted using Foucault's governmentality writings, which encourage us to look beyond the juridical epistemologies of international relations and international law, but not beyond the interlacing of laws and norms, here explored through interwar League governmentalities.